Studies on Schismatoglottideae (Araceae) of Borneo XXXV – Seven New species of Aridarum - Wong, Sin Yeng; Boyce, P.C; Low, Shook Ling (International Aroid Society, Inc., 2014)
Seven new species of Aridarum are described and illustrated: Aridarum pendek S.Y.Wong, S.L.Low & P.C.Boyce and A. velutandrum S.Y.Wong, S.L.Low & P.C. Boyce [Sarawak, Malaysian Borneo]; A. alatense S.Y.Wong, S.L.Low & P.C.Boyce, A. surukense S.Y.Wong, S.L.Low & P.C. Boyce, and A. zygosetum S.Y.Wong, S.L.Low & P.C.Boyce [Kalimantan Barat and Kalimantan Tengah, Indonesian Borneo]; and A. hebe S.Y.Wong, S.L.Low & P.C.Boyce [Kalimantan Utara, Indonesian Borneo]. Aridarum caulescens var. angustifolium Bogner & Nicolson is shown to represent a further undescribed species from Sarawak, and is here published as Aridarum orestum S.Y.Wong, S.L.Low & P.C.Boyce. Together these seven novelties take the genus Aridarum to 21 accepted, described species. An identification key to all species is provided.